2001
DOI: 10.2307/3434699
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Lead and Induction of Genetic Damage

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The National Institute of Environmental Health Sciences (NIEHS) and Brogan & Partners are collaborating with JSTOR to digitize, preserve and extend access to Environmental Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…They observed that frequency of chromosomal aberrations and sister chromatid exchanges increased significantly with the Table 1 Summary (mean±SD) of Pb-B (μg/dl) and frequencies (counts per 3,000 cells) of micronuclei and nuclear changes in buccal epithelial cells of control and exposed subjects rise of lead concentrations in urine, showing a linear correlation. (Vaglenov et al 2001) had found genotoxic effect of lead by the MNT. Investigations of lead exposure in outdoor painters revealed high level of CA and SCE in lymphocytes and elevated MN in buccal cells (Pinto et al 2000).…”
Section: Discussionmentioning
confidence: 94%
“…They observed that frequency of chromosomal aberrations and sister chromatid exchanges increased significantly with the Table 1 Summary (mean±SD) of Pb-B (μg/dl) and frequencies (counts per 3,000 cells) of micronuclei and nuclear changes in buccal epithelial cells of control and exposed subjects rise of lead concentrations in urine, showing a linear correlation. (Vaglenov et al 2001) had found genotoxic effect of lead by the MNT. Investigations of lead exposure in outdoor painters revealed high level of CA and SCE in lymphocytes and elevated MN in buccal cells (Pinto et al 2000).…”
Section: Discussionmentioning
confidence: 94%
“…In this study, a significant increase in the frequency of chromosomal aberrations, satellite associations, DNA damage and micronuclei in the buccal epithelial cells was observed in exposed subjects as compared to control individuals. In earlier reports, an increased incidence of micronuclei in peripheral lymphocytes was observed in a group of 22 lead workers whose mean BLL was 61 g/dl relative to control groups with mean BLLs of 18-28 g/dl [31,32]. Battery plant workers (n = 37) had significantly elevated levels of DNA breaks in lymphocytes compared to unexposed subjects (n = 29) [30].…”
Section: Tablementioning
confidence: 85%
“…Lead is a toxic element for human and animal organisms (Adonaylo & Oteiza 1999;Ye et al 1999;Vaglenov et al 2001). Its negative impact on reproduction is well known (Thoreux-Manlay et al 1995;Alexander et al 1996;Gandley et al 1999).…”
mentioning
confidence: 96%